Potentials for Establishing Collaborative Virtual Reference Services at the University of Dar es Salaam and Constituent College Libraries - Kassim, Mohamed; Ndumbaro, Faraja; Wema, Evans; Mbilinyi, Debora; Bitebo, Ally (University of Dar es Salaam Library Journal, 2025)
This study evaluates the feasibility of establishing collaborative virtual reference services between the University of Dar es Salaam library and its constituent college libraries. Using qualitative and quantitative methods, the study found that many library users utilise electronic devices for various purposes, including accessing library services, indicating readiness for virtual services. The study suggests various virtual reference options, including Zoom, email, real-time chat, social media, and web forms, along with the necessary technological infrastructure. Despite challenges such as understaffing and unreliable internet, the libraries have a skilled workforce with vast experience in delivering reference services. The weaknesses identified in this study underscore the necessity for the University library and its constituent college libraries to collaboratively pool their resources to offer more efficient and cost-effective virtual reference services. This would enhance the fundamental functions of their parent institution, that is, teaching, research, consultancy, and community services. Overall, given the confirmation of the libraries’ strong IT infrastructure, skilled personnel, and established track record in reference service provision, it can be concluded that the libraries are well-prepared to implement collaborative virtual reference services that cater to the varied needs of their users. Keywords: Reference service, Virtual reference service, Collaborative reference services, Library services, Academic libraries, Tanzania https://dx.doi.org/10.4314/udslj.v20i1.2